The reasons for architectural monuments destruction and methods of capacity reinforce for bases and fundaments - Orlenko, Mykola (КНУБА, 2017)
The main problem of monuments’ emergency state is poor condition of the bases and foundations often due to their moisture. Uneven foundations subsidence leads to redistribution of efforts in bearing constructions and static instability of the base-foundation-building system. That’s why any restoration starts with the removal of their emergency state. Using the example of Mykola Pritisk’s Church on Podil, where groundwater underflooding caused the collapse in the south-eastern part of the building, describes how the restoration works on the monument, which began with the reinforcement of damaged foundations and framework for static recovery of base-foundation-building system, measures to protect foundations and basements from underflooding, ensuring reliable vertical and horizontal waterproofing for the basement walls and floors, and all the underground part of the church, and works for antiseptic treatment of bio-damaged and saline walls and plaster surfaces. After that, the organization of reliable geodetic control for the structure deformation was ensured.
Keywords: bases and fundaments; groundwater; intensification; 72.03; 624.159.4